A novel and efficient bioprocess from steam exploded corn stover to ethanol in the context of on-site cellulase production. (15th March 2017) - Zhao, Chen; Zou, Zongsheng; Li, Jisheng; Jia, Honglei; Liesche, Johannes; Fang, Hao; Chen, Shaolin
Abstract: Saccharomyces cerevisiae, a recombinant S. cerevisiae, Pichia stipistis and an adapted P. stipistis were compared in fermenting steam exploded corn stover (SECS) enzymatic hydrolysate, which contained glucose and xylose, among which S. cerevisiae was found to be the most efficient. The residual xylose in the fermentation broth of S. cerevisiae was concentrated during the distillation of ethanol and fermented by xylose-fermenting yeasts, among which the adapted P. stipistis was found to be the best. As a result, a novel and efficient bioprocess from SECS to ethanol was established, producing approximately 27.00 g ethanol from 111.51 g SECS with an ethanol production rate of 2.50 g/L/h and a yield of 0.24 g ethanol/g SECS, and 58.18 g ethanol from 341.45 g SECS with an ethanol production rate of 2.31 g/L/h and a yield of 0.17 g ethanol/g SECS. Highlights: A novel and efficient bioprocess from SECS to ethanol was successfully established. On-site cellulase production was done by the mixed culture of T. reesei and A. niger. S. cerevisiae was the most robust in the fermentation of SECS enzymatic hydrolysate. The adapted P. stipistis was the most robust in fermenting the distillation residue. Xylose-fermenting S. cerevisiae was constructed and P. stipistis was adapted.